2018
DOI: 10.1097/med.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Androgen abuse epidemiology

Abstract: From the 1970s, androgen abuse spread from athletes into the general population. Consistent with previous evidence, reviewed studies suggest that androgen abuse epidemiology and prevalence is higher in Western cultural contexts, the Middle East, and South America (Brazil) and lower in Africa and Asia. Evidence also corroborates indications that androgen abuse is less prevalent among women (vs. men), and in the general population in contrast to particular subpopulations consisting of athletes, injection drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…2 Testosterone replacement therapy (TRT) prescriptions in the US decreased by 50% between 2013 and 2016,3 but remain well above the levels needed to treat pathological hypogonadism 4. Since the 1970s, use of anabolic steroids has spread from athletes to the general population,5 with a lifetime prevalence rate of 6.4% for men 6…”
Section: Introductionmentioning
confidence: 99%
“…2 Testosterone replacement therapy (TRT) prescriptions in the US decreased by 50% between 2013 and 2016,3 but remain well above the levels needed to treat pathological hypogonadism 4. Since the 1970s, use of anabolic steroids has spread from athletes to the general population,5 with a lifetime prevalence rate of 6.4% for men 6…”
Section: Introductionmentioning
confidence: 99%
“…Some studies assessed the prevalence of AAS use among resistance training practitioners in gyms, resulting in a prevalence range of 4.5 to 24.9% (Pellegrini et al, 2017). Moreover, this kind of drug is commonly used by other categories such as recreational sportspeople, and sexual and gender minorities (Sagoe and Pallesen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Weight-lifters and body-builders were the first athletes to use AAS in sports competitions and later, other athletes followed suit (Griffin and Wilson, 1998). In the early 1980s, AAS use began to spread to individuals engaged in recreational sports, for the purpose of improving body-image (www.drugabuse.gov/publications/research-reports/anabolic-steroid-abuse), as well as intravenous drug users, and sexual and gender minorities (Sagoe and Pallesen, 2018). Unfortunately, there are now millions of AAS users worldwide, with most using them to become leaner and more muscular and not for competitive purposes (Parkinson and Evans, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that AAS abuse is more prevalent in Western countries, the Middle East and Brazil and is less prevalent in Africa and Asia (Sagoe and Pallesen, 2018). Prior to initiation of AAS, users are more likely to be participants in sports, have malfunctioning relationships, psychopathologies, suffer from low self-esteem, negative body image, deviant behavior and history of abusing other drugs, deteriorating school performance and certain personality disorders.…”
Section: Introductionmentioning
confidence: 99%